Analysis of The Relationship Between Personal Hygiene Practices of Mothers and Toddlers with The Incidence of Stunting in Paluh Sibaji Village, Pantai Labu Sub-District - Putri Ayu Patricia Manurung; Sri Malem Indirawati; Umi Salmah; Angellika Sarumaha; Ami sary veronika Tinambunan; Annisa Rizka Lestari (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2025)
Deli Serdang Regency is a region that contributes to stunting rates in North Sumatra Province, with a stunting prevalence of 13.9% in 2022, a 1.4% increase from 2021. Personal hygiene is an individual factor that can contribute to stunting when associated with infectious triggers. This study aims to analyze the relationship between maternal and toddler personal hygiene and stunting in toddlers in Paluh Sibaji Village. This type of research is analytical with a cross-sectional study design. The population is 375 mothers with a sample size of 141 calculated based on the Lameshow formula using cluster sampling techniques. The chi-square test results showed that maternal personal hygiene had a p-value of 0.567, while toddler personal hygiene had a p-value of 0.228. The results showed no significant relationship between maternal and toddler personal hygiene and stunting. Stunting is caused by other factors not studied. Recommendations for mothers of toddlers include meeting protein needs and maintaining personal hygiene.